Sniper shield - Bowen, Carl (Bowen, Carl. Shadow Squadron., 2013)
The elite US sniper team of Shadow Squadron's latest mission is to protect Heshem Shadid, ex-terrorist who has turned politician and now is on the side of the US, and a target for his former terrorist friends.